Islam, Migration and Jinn
IX, 254 p. 2 illus.
Keywords: This book explores the agency of Jinn, the so-called “demons of Islam”. They are regarded as mostly invisible and highly mobile creatures. In a globalized world with manifold forms of forced and voluntary migrations, Jinn are likewise on the move, interfering in the human world and affecting the mental and physical health of Muslims. This continuous challenge has so far been mainly addressed by traditional Muslim health management and by the so-called spiritual medicine or medicine of the Prophet. This book shifts perspective. Its interdisciplinary chapters deal with the transformation of manifold cultural resources by first analyzing the doctrinal and cultural history of Jinn and the treatment of Jinn affliction in Arabic texts and other sources. It then discusses case studies of Muslims and current health management approaches in the Middle East, namely in Egypt and Syria. Finally, it turns to the role of Jinn in a number of migratorysettings such as Spain, Denmark, Great Britain and Guantanamo. Annabelle Böttcher is Vice President, Dean of the Faculty of Social Work and Professor at the Duale Hochschule Baden-Württemberg in Villingen-Schwenningen, Germany, and Adjunct Professor at the University of Southern Denmark in Odense, Denmark. Her current research interests lie at the intersection of Islamic culture, health, (forced) migration and war. Birgit Krawietz is Professor of Islamic Studies at Freie Universität Berlin and the Berlin Graduate School Muslim Cultures and Societies, Germany. Her research focuses on Islamic law and medical ethics, cultural history, body and sports, the Arab Gulf region and Turkey.